텍스트마이닝을 활용한 부산 부동산 시장 인식 변화 연구 - 이지백(Ji-Beak Lee) (인문사회과학연구, 2024)
· 연구 주제: 본 연구는 텍스트 마이닝 기법을 활용하여 부산 부동산 시장에 대한 대중의 인식 변화를 분석하는 데 그 목적이 있다. 이를 위해 뉴스, 소셜 미디어, 정부 정책 자료 등 다양한 텍스트 데이터를 수집하여 부산 부동산 시장과 관련된 주요 키워드, 감정 분석, 그리고 시간에 따른 인식 변화 추이를 살펴보고자 한다. 이를 통해 부산 부동산 시장에 대한 심층적인 이해를 도모하고, 향후 시장 예측 및 정책 개발에 기여하고자 한다. · 연구 배경: 부동산 시장은 경제적, 사회적 요인에 민감하게 반응하며, 정책변화, 경제상황, 지역 특성에 따라 시장 참여자들의 인식이 변동된다. 최근 텍스트 마이닝 기법의 발전으로 대중의 인식을 분석할 수 있는 새로운 방법론이 부상하고 있다. 특히, 부산 부동산 시장은 서울 및 수도권에 비해 상대적으로 독립적인 변화 양상을 보이며, 지역 특성에 따라 부동산 시장에 대한 다양한 인식이 존재해왔다. 이를 파악하는 것은 향후 부동산 정책 수립 및 시장 예측에 중요한 정보를 제공할 수 있다. · 선행연구와의 차이점: 기존의 부동산 시장 연구는 주로 실물 데이터나 경제적 지표를 기반으로 한 분석에 중점을 두었다. 그러나 본 연구는 대중의 인식 변화에 초점을 맞추어 텍스트 마이닝이라는 분석기법을 적용한다는 점에서 차별성을 지닌다. 또한, 지역적으로도 부산을 중심으로 한 연구는 상대적으로 부족한 상황에서, 부산 부동산 시장의 독특한 특성과 대중의 인식 변화를 분석한다는 점에서 기존 연구들과 차별화된다. · 연구방법: 본 연구는 데이터를 심층적으로 분석하기 위해 다섯 가지 텍스트 분석 기법을 활용하였다. 먼저, TF-IDF 분석을 통해 문서 내 단어의 중요도를 평가하고, N-gram 분석으로 단어 패턴을 파악하였다. 또한, LDA 토픽 모델링을 사용하여 문서에서 숨겨진 주제를 식별하고, 부산 부동산 시장에 관한 주요 토픽을 제시하였다. 또한 네트워크분석을 통해 키워드 간 연관성을 제시하였으며, 마지막으로 긍부정 분석을 통해 부산 부동산시장에 대한 인식을 조사하였다. · 연구결과: 텍스트마이닝 5가지 기법을 활용하여 다각도에서 분석한 결과, 부산 부동산 시장은 인구의 유출과 노령화로 인해 점차 쇠퇴해가고 있으며, 이에 대한 사람들의 전망과 인식도 긍정적이지 못한 것으로 파악되었다. · 공헌점 및 기대효과: 첫째, 정책 결정자들에게는 대중의 인식과 반응을 바탕으로 보다 정교한 부동산 정책을 설계하는 데 도움을 줄 수 있다. 둘째, 시장 참여자들에게는 부동산 시장의 인식 변화에 따른 투자 전략 수립에 유용한 인사이트를 제공할 수 있다. 셋째, 학문적으로는 텍스트 마이닝 기법을 지역 부동산 시장 연구에 적용한 사례로서, 향후 연구에 기초자료로 활용될 수 있다. · Research topics: This study aims to analyze the change in public perception of the Busan real estate market using text mining techniques. To this end, we will collect text data such as news, social media, and government policy data to examine major keywords related to the Busan real estate market, emotional analysis, and changes in perception over time. Through this, we intend to promote an in-depth understanding of the Busan real estate market and contribute to future market prediction and policy development. · Research background: The real estate market reacts sensitively to economic and social factors, and the perception of market participants changes according to policy changes, economic conditions, and regional characteristics. With the recent development of text mining techniques, a new methodology for analyzing public perceptions is emerging. In particular, the Busan real estate market shows relatively independent changes compared to Seoul and the metropolitan area, and various perceptions of the real estate market have existed according to regional characteristics. Understanding this can provide important information for future real estate policy establishment and market prediction. · Differences from prior research: Existing real estate market research mainly focused on analysis based on real data or economic indicators. However, this study is differentiated because it applies text-mining analysis techniques, focusing on changes in public perception. In addition, locally, research focusing on Busan is differentiated from existing studies in that it analyzes the unique characteristics of the Busan real estate market and changes in public perception in a relatively insufficient situation. · Research method: This study used five text analysis techniques to deeply analyze the data. First, the importance of words in the document was evaluated through TF-IDF analysis, and word patterns were identified through N-gram analysis. In addition, LDA topic modeling was used to identify hidden topics in the document, and major topics about the Busan real estate market were presented. In addition, the relationship between keywords was presented through network analysis, and finally, the perception of the Busan real estate market was investigated through positive and negative analysis. · Research results: As a result of analyzing from various angles using five text mining techniques, it was found that the Busan real estate market is gradually declining due to the outflow of the population and aging, and people's prospects and perceptions about it are also not positive. · Contribution points and expected effects: First, policymakers can help design more sophisticated real estate policies based on public perceptions and reactions. Second, it can provide useful insights to market participants in establishing investment strategies according to changes in the perception of the real estate market. Third, academically, as an example of applying text mining techniques to local real estate market research, it can be used as basic data for future research. KCI Citation Count: 0